Teacher Training as an Obligation to Prevent Sexual Violence against Children: Meeting International Standards - Ramírez González, Alejandra (The Age of Human Rights Journal, 2025)
This paper holds that teacher training constitutes a binding preventive obligation arising from Articles 19 and 34 of the Convention on the Rights of the Child, Article 5 of the Lanzarote Convention, and Article 23(3) of Directive 2011/92/EU. Subsequently, the main international standards behind of it are identified, encompassing requirements for initial and continuous certification, detection and reporting capacities, and regular evaluation. Analysis of the level of compliance with this obligation reveals a context of shortcomings that has led to the implementation of civil society initiatives aimed at reducing the gap. In this context, the article briefly presents a local teacher training project on the prevention of sexual violence as a good practice that can be replicated.